Perioperative Management of Endocrine Active Adrenal Tumors - Schreiner, Florentine; Anand, Gurpreet; Beuschlein, Felix (Experimental and Clinical Endocrinology & Diabetes, 2019)
Endocrine active adrenal tumors are associated with a relevant risk of complications during surgery, either due to direct hemodynamic effects of the hormone excess or due to hormone related comorbidities. Over the last decades, careful preoperative evaluation and improved peri-interventional medical management of affected patients has resulted in a significant reduction of perioperative complications. In addition, improvement in anesthesia and surgical techniques with the feasibility of laparoscopic adrenalectomy have contributed to reduce morbidity. Nevertheless, there are still several challenges to be considered in the perioperative care of these patients. Due to the rarity of functionally active adrenal tumors, there are no prospective data available to guide clinical management. Accordingly, most recommendations are based on retrospective data analysis, expert opinion or carry weak evidence based on small series or case reports. The aim of this review is to summarize the current knowledge and to suggest practical approaches to reduce perioperative complications in endocrine active adrenal tumors. This review exclusively deals with data from adult patients with functionally active adrenal tumors.
Keywords: pheochromocytoma; paraganglioma; primary aldosteronism; Cushing’s syndrome; surgery; laparoscopy; perioperative management